Design and synthesis of galactose-conjugated fluorinated and non-fluorinated proline oligomers: towards antifreeze molecules. Issue 70 (13th August 2018) - Sumii, Yuji; Hibino, Hayata; Saidalimu, Ibrayim; Kawahara, Hidehisa; Shibata, Norio
Abstract : Galactose-conjugated fluorinated and non-fluorinated proline oligomers were synthesized and evaluated as antifreeze molecules. Abstract : Galactose-conjugated fluorinated and non-fluorinated proline oligomers that exhibit an α-helical structure with hydrophilic and lipophilic parts were designed as potential antifreeze molecules. These galactose-proline oligomers were synthesized and their physical properties were evaluated. Interestingly, the non-fluorinated galactose-proline oligomers showed in contrast to the fluorinated analogues weak antifreeze activity. The difference in antifreeze activity should be attributed to the fluorine gauche effect, which should induce a conformation in fluorinated prolines that is different from that of natural proline. The results obtained in this study thus suggest that the 3D conformation of the galactose-conjugated fluorinated and non-fluorinated proline oligomers is very important for their anti-freezing properties.